2002
DOI: 10.1046/j.0032-0862.2001.00650.x
|View full text |Cite
|
Sign up to set email alerts
|

Following the dynamics of strobilurin resistance in Blumeria graminis f.sp. tritici using quantitative allele‐specific real‐time PCR measurements with the fluorescent dye SYBR Green I

Abstract: Strobilurin-resistant isolates of Blumeria ( Erysiphe ) graminis f.sp. tritici , the cause of wheat powdery mildew, were more than 10-fold less sensitive to azoxystrobin than sensitive isolates. In all resistant isolates, a mutation resulting in the replacement of a glycine by an alanine residue at codon 143 (G143A) in the mitochondrial cytochrome b gene was found. Allele-specific primers were designed to detect this point mutation in infected wheat leaves. Using quantitative fluorescent allele-specific real-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
91
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(92 citation statements)
references
References 37 publications
(47 reference statements)
1
91
0
Order By: Relevance
“…In most cases, the degree of sensitivity of fungal populations to one or more fungicides is assessed by biological methods. Sierotzki et al, 2000) and on the opposite some of them on populations, where resistance allele is quantify in gDNA pools by using Real time PCR technologies (Benzimidazole resistance in Sclerotinia sclerotiorum Chen et al, 2009 ; Strobilurins resistance on Blumeria graminis Fraaije et al, 2002 and Pyrenophora teres Kianianmomeni et al, 2007). However, one limitation of this method concerns the nonspecific amplification of alleles, which may affect precision.…”
Section: Fenhexamid Monitoring In Fields: a Molecular Approachmentioning
confidence: 99%
“…In most cases, the degree of sensitivity of fungal populations to one or more fungicides is assessed by biological methods. Sierotzki et al, 2000) and on the opposite some of them on populations, where resistance allele is quantify in gDNA pools by using Real time PCR technologies (Benzimidazole resistance in Sclerotinia sclerotiorum Chen et al, 2009 ; Strobilurins resistance on Blumeria graminis Fraaije et al, 2002 and Pyrenophora teres Kianianmomeni et al, 2007). However, one limitation of this method concerns the nonspecific amplification of alleles, which may affect precision.…”
Section: Fenhexamid Monitoring In Fields: a Molecular Approachmentioning
confidence: 99%
“…In most cases, resistance has been shown to be associated with point mutations in the ␤-tubulin gene which result in altered amino acid sequences at the benzimidazole binding site (13). Studies with laboratory mutants of Aspergillus nidulans, Neurospora crassa, and Saccharomyces cerevisiae showed that changes at codons 6,50,134,165,198,200, and 241 in the ␤-tubulin gene were responsible for benzimidazole resistance (13). In contrast to laboratory mutants, most field isolates of plant-pathogenic fungi exhibit codon changes that, strikingly, seem to be restricted to positions 50 (22), 198, 200 (1,13), and 240 (1).…”
mentioning
confidence: 99%
“…1) binds with a hydrogen bond to the amide group of glutamic acid at position 272 in domain C; therefore, this region plays an important role in accepting fungicides. Since substitution of glycine for alanine at position 143 (G143A) in domain B significantly lowers the affinity of strobilurin fungicides to cytochrome b, 7,8,13,14,[19][20][21][22][23] interaction between domain B and strobilurin fungicides must be strong. On the other hand, substitution of phenylalanine for leucine at position 129 (F129L) in domain A has been shown not to significantly lower the affinity of strobilurin fungicides to cytochrome b.…”
Section: Discussionmentioning
confidence: 99%